ISTOPATHOLOGY OF THE BRAIN OF WHITE RATS UPON ADMINISTRATION OF MIMOSIN FROM SIMPLISIA OF LEUCAENA LEAVES - Ningsih, Yuyun Setia; Berata, I Ketut; Setiasih, Ni Luh Eka; Kardena, I Made; Samsuri,; Merdana, I Made (Buletin Veteriner Udayana, 2025)
Lamtoro (Leucaena leucocephala) is a widely used cattle feed in Indonesia due to its high protein, flavonoid, and tannin content. However, it contains mimosine, a compound whose effects on the liver remain poorly understood. This study aimed to investigate the histopathological effects of mimosine on the liver of experimental animals. Twenty male Wistar rats (Rattus norvegicus), aged 2 months (150–200 g), were divided into four groups: a negative control (P0), a positive control given pure mimosine (5 mg/head/day, P1), and two groups administered mimosine from lamtoro leaf simplisia at 50 mg/head/day (P2) and 150 mg/head/day (P3). Treatments were administered orally for 14 days. On day 15, liver samples were collected, fixed in 10% neutral buffered formalin (NBF), and processed for histopathological analysis using hematoxylin-eosin (H&E) staining. Lesions (congestion, inflammation, and necrosis) were scored on a scale of 0 (normal) to 3 (severe). Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. Results showed that pure mimosine (5 mg) and lamtoro simplisia (50 mg and 150 mg) induced significant hepatic congestion compared to controls, while inflammation was not statistically significant. Necrosis was not observed in any group. No significant difference was found between the two doses of lamtoro simplisia. These findings suggest that mimosine, whether pure or derived from lamtoro leaves, induces mild to moderate liver damage, primarily congestion, but further research is needed to clarify its long-term effects.